A Discourse Historical Analysis of Identity Construction in Becoming (2018) by Michelle Obama - Melenia Savhira; Junaidi Junaidi (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2022)
Research on identity through written narrative has been popular in the linguistics field over the decades. In this paper, a famous memoir written by Michelle Robinson Obama, Becoming (2018), is examined to analyze the construction of identities. This memoir is chosen because of the strong personal narrative and inspiring story which recounts the struggle of the African American woman against discrimination in the United States. This paper focuses on Becoming Us, which is examined through the Discourse-Historical Analysis (DHA) by Ruth Wodak. This approach offers several discursive strategies, some of which are referential/nomination and predication that are applied to analyze the linguistic features which provide positive, negative, and neutral representations of the social actor. All of these representations contribute to construct Michelle Obama’s cultural and racial identities. The novelty of this research lies in a more linguistic approach and historical context as the endeavors to examine the identities.